2020
DOI: 10.1021/acsomega.0c02913
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Induced Interfacial Transcrystallization of Single-Fiber Milkweed/Polycaprolactone/Polyvinylchloride Composites

Abstract: Understanding the interfacial crystallization is crucial for semi-crystalline polymer/natural fiber composites because it links to the final properties. This work reports, for the first time, the interfacial crystallization of a miscible blend between polycaprolactone (PCL) and polyvinylchloride (PVC) with milkweed fibers. We have first described the morphology of the fibers and the chemical composition of waxes covered on its surface. Our findings show that the transcrystallization (TC) layer of PCL/PVC could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The spherulites of PLLA‐ b ‐PCL‐ b ‐PLLA3.0 triblock copolymer show ring‐banded textures. The reason for the formation of ring‐banded spherulites may be the twist of the lamellar chains around their growth axis, which could result in a change of the refraction index depending on the orientation of the crystalline planes 48–50 . Another possible reason is the rhythmic change in the thickness of the spherulites during growth, resulting in regular extinction bands 49 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spherulites of PLLA‐ b ‐PCL‐ b ‐PLLA3.0 triblock copolymer show ring‐banded textures. The reason for the formation of ring‐banded spherulites may be the twist of the lamellar chains around their growth axis, which could result in a change of the refraction index depending on the orientation of the crystalline planes 48–50 . Another possible reason is the rhythmic change in the thickness of the spherulites during growth, resulting in regular extinction bands 49 .…”
Section: Resultsmentioning
confidence: 99%
“…The reason for the formation of ring-banded spherulites may be the twist of the lamellar chains around their growth axis, which could result in a change of the refraction index depending on the orientation of the crystalline planes. [48][49][50] Another possible reason is the rhythmic change in the thickness of the spherulites during growth, resulting in regular extinction bands. 49 A previous investigation 50 has found that the band spacing and regularity of ring bands decrease with increase of the molecular weight of PLA blocks.…”
Section: Spherulitic Morphology Of Supramolecular Polymers During Iso...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a crystallizable component in the blend may disturb the crystallization of the host polymer matrix. The final morphology may be kinetically controlled by the crystallization condition, thermal history, and composition as described in our previous publications. …”
Section: Introductionmentioning
confidence: 99%